2021
DOI: 10.1177/24705470211051327
|View full text |Cite
|
Sign up to set email alerts
|

Research on Posttraumatic Stress Disorder in the Context of the COVID-19 Pandemic: A Review of Methods and Implications in General Population Samples

Abstract: Increasing concern about the mental health sequelae to the COVID-19 pandemic has prompted a surge in research and publications on the prevalence of posttraumatic stress disorder in general population samples in relation to the pandemic. We examined how posttraumatic stress disorder in the context of the COVID-19 pandemic has been studied to date and found three general themes: (1) assessment of posttraumatic stress disorder and posttraumatic stress disorder symptoms relied on self-report measures and often did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…Because of the offensive effects of this serious, wide-spreading disease, the literature has extensively described the COVID-19 pandemic as a collective trauma, which has been associated with a global increase in PTSD symptoms in different population groups [ 3 , 7 , 12 , 13 , 14 , 15 ]. Methodological flaws in studies on COVID-19-related trauma have been spotted, such as the use of improper/outdated measures, cross-sectional design, and self-report methods of data collection [ 41 , 42 , 43 , 44 ]. Nonetheless, variations in PTSD symptom clusters in people exposed to various trauma have been revealed by different robust statistical methods [ 15 , 24 , 35 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the offensive effects of this serious, wide-spreading disease, the literature has extensively described the COVID-19 pandemic as a collective trauma, which has been associated with a global increase in PTSD symptoms in different population groups [ 3 , 7 , 12 , 13 , 14 , 15 ]. Methodological flaws in studies on COVID-19-related trauma have been spotted, such as the use of improper/outdated measures, cross-sectional design, and self-report methods of data collection [ 41 , 42 , 43 , 44 ]. Nonetheless, variations in PTSD symptom clusters in people exposed to various trauma have been revealed by different robust statistical methods [ 15 , 24 , 35 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Same as in many other studies, PTSD symptoms were self-reported in a cross-sectional design [ 44 ], and COVID-19 was assumed to be a collective traumatic event without a verified assessment of whether it was perceived as a direct trauma exposure (criterion A) according to DSM-5 [ 44 ]. A large body of knowledge indicates that considering COVID-19–related PTSD as a diagnosis is questionable regarding PTSD definitions in the ICD-11 and DSM-5 [ 41 , 42 , 44 ]. In this respect, the inclusion of participants who do not consider COVID-19 as trauma may have a dilution effect on COVID-19–related PTSD diagnosis in our samples [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the available research shows that the search for such personality traits is quite limited and refers mainly to individuals who are already diagnosed as suffering from PTSD. 26,27 These individuals tend to score high on neuroticism which is robustly related to many mental disorders. 28,29 Crestani et al report further that PTSD is positively correlated with harm avoidance and self-transcendence, and negatively correlated with self-directedness.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that those psychologically vulnerable before the pandemic or with pre-existing mental and physical health conditions are more likely to report extreme COVID-19-related stressors (Alonzi et al, 2020; Barone et al, 2023; Franic, 2021; Husky et al, 2021; Manchia et al, 2022). Brailovskaia and Margraf (2020) found that pre-pandemic stress among adults predicted COVID-19-related burden at the beginning of the pandemic.…”
Section: Introductionmentioning
confidence: 99%